1997
DOI: 10.1021/ja971866g
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences of 2-Phenethylamines. A Computational Study of Substituent and Solvent Effects on the Intramolecular Amine−Aryl Interactions in Charged and Neutral 2-Phenethylamines

Abstract: A computational investigation of the conformational preferences of 2-phenethylamine has been carried out with a variety of techniques. To determine the intrinsic (in the absence of a solvent medium) conformational preferences of the 2-phenethylamine system, ab initio calculations at various levels of theory up to the MP2/6-311+G(d,p)//MP2/6-31G(d,p) level were carried out. This is the most sophisticated level of theory that has been applied to this biologically important system to date. In the absence of a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
(47 reference statements)
3
41
0
Order By: Relevance
“…It has been shown that the most stable conformer of phenethylammonium has a gauche confirmation of the NH 3 + -group with respect to the alkyl chain, in which one hydrogen atom of the NH 3 + -group is oriented towards the benzene ring. 53 In the excited state of this molecule, this hydrogen atom is situated closer to the benzene ring. 54 Therefore, UV illumination could weaken the hydrogen bonding between PEA and the chloride ions.…”
Section: àmentioning
confidence: 96%
“…It has been shown that the most stable conformer of phenethylammonium has a gauche confirmation of the NH 3 + -group with respect to the alkyl chain, in which one hydrogen atom of the NH 3 + -group is oriented towards the benzene ring. 53 In the excited state of this molecule, this hydrogen atom is situated closer to the benzene ring. 54 Therefore, UV illumination could weaken the hydrogen bonding between PEA and the chloride ions.…”
Section: àmentioning
confidence: 96%
“…5 and 8 for the definition of gauche and trans). 6,9 In contrast, calculations for isolated neutral and protonated dopamine demonstrate the energetic preference for the gauche conformation. 6,8,9 In the latter case, this is largely due to the favourable interaction of the positively charged ammonium group with the p electron system of the aromatic ring (NH-p interaction).…”
Section: Introductionmentioning
confidence: 93%
“…6,9 In contrast, calculations for isolated neutral and protonated dopamine demonstrate the energetic preference for the gauche conformation. 6,8,9 In the latter case, this is largely due to the favourable interaction of the positively charged ammonium group with the p electron system of the aromatic ring (NH-p interaction). 6,9 In contrast, the analysis of the crystal structure and IR spectra of neutral dopamine in the condensed phase yields a trans conformation, which is rationalized by the stronger stabilization through solvation when compared to the gauche conformation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…21 All others were developed following Kollman 22 and Hopfinger 23 procedures. In order to develop suitable parameters for N -H· · ·N hydrogen bonding, ab initio calculations at STO-3G 24 level were used for calculating atomic charges compatible with the AMBER field ones, as Urban et al 25 claimed that they gave excellent results for the study of ammonium interactions. In all cases, geometries were minimized to a maximun energy gradient of 0.1 kcal/mol using the Polak -Ribiere algorithm, and simulated annealing procedure was used to cover all conformational space running molecular dynamics at 400 K. To optimize host -guests interactions the cation was moved and/or rotated and docked into the cavity of the ligand in all possible positions and then minimized the energy of the complex with no restraints.…”
Section: Molecular Modellingmentioning
confidence: 99%